Actin expression in the sensorimotor cortex of the cerebral hemispheres during modeling of the transient ischemia and after immunocorrection. - Yaremenko, L. M.; Grabovoy, A. N.; Slichna, G. M.; Chukhrai, S. N.; Slichniy, I. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Mammalian brain is characterized by significant actin content. Actin is involved in the formation of microfilaments that make up the cytoskeleton in neurons. Objective. Explore the particular expression of actin in the sensorimotor cortex of the brain under conditions of circulatory disorders and correction of neurodegenerative changes by immunomodulation. Methods. Research was conducted on 150 white male adult Wistar rats weighing 260-290 g. The brains were taken for investigation after 1, 3, 10, 30 and 90 days after the start of the experiment. Histological, immunohistochemical, statistical methods and the densitometry were used. Results. Observations have shown that murine monoclonal anti-smooth muscle actin (clone 1A4, Dako, Denmark) can be used to detect actin in the brain of rats. Discirculatory changes that were identified in pseudo-operated rats as well as in rats with ligation of the carotid artery did not produce significant changes in the expression of actin in the sensorimotor cortex. Application of imunofan demonstrated some of its protective properties towards reducing actin expression as a result of ischemia, and provide faster rate of recovery. It could be associated with a restoration of functioning synapses and the formation of cones of growth after the terminal autoneurotomy result of ischemic injury. Conclusion. Murine monoclonal antibody against smooth muscle actin (clone 1A4, Dako, Denmark) can be used to detect actin in the brain of rats. Transient circulatory disorders reduce the expression of actin in sensorimotor cerebral cortex, the restoration of which there is only a remote period. Application of imunofan on the background of circulatory disorders leads to less distinct reduction in actin expression sensorimotor cerebral cortex of the brain and significantly accelerates its recovery.